BAGAIMANA MENINGKATKAN MOTIVASI UNTUK MEMPERBAIKI HASIL BELAJAR SISWA? - Zaki, Mochammad Choirul; Saptono, Ari; Dianta A. S., Karuniana (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2024)
Education in Indonesia is organized by taking into account the different characteristics and needs of learners. The education process prioritizes the interests and talents of students. At SMA Dewi Sartika, SMA Muhammadiyah 5, and SMA 17 Agustus 45, the learning outcomes of economics subjects show low completeness, namely 34%, 37%, and 35%. The contributing factors include students' lack of self-efficacy and self-regulation, as well as low learning motivation. This study aims to determine the effect of self-efficacy and self-regulation on economic learning outcomes with learning motivation as an intervening variable. The study population was grade X students in the 2022/2023 school year in the three high schools, with a sample of 225 students. Data were collected through questionnaires and analyzed using path analysis with the IBM SPSS 25.0 program. The results showed a positive and significant influence between self-efficacy and self-regulation on economic learning outcomes through learning motivation.